Changes of the smooth endoplasmic reticulum induced by rifampicin in human and guinea-pig hepatocytes. Issue 12 (December 1971) - Jezequel, A. M.; Orlandi, F.; Tenconi, L. T.
Abstract : Rifampicin induces a proliferation of the smooth endoplasmic reticulum in guinea-pig and human hepatocytes. This may support the hypothesis of enhancement of drug-metabolizing enzymes induced by the drug. However, the pattern of proliferation is not similar in man and in guinea-pig hepatocytes. Some caution is needed in the study of enzyme induction in man and in extrapolations from animal to human data.